Reshaping Political Leadership in Nigeria in the Light of Ibuanyidanda Philosophy - Ikegbu, Ephraim Ahamefula; Iwuchuckwu, Godwin C. S. P.; Bisong, Peter B. (Program Studi Sosiologi, 2019)
This paper sees the leadership problem in Nigeria (which is motivated by the pursuit of personal gains and comfort) as a major consequence of economic slowdown in Nigeria. It argues that the Nigerian leaders, past and present, have consciously and without any form of regret to its attendant negative consequences built the psychology of polarisation, bifurcation, ethnic sentiment and the growing mind-set of the nearer the better and the safer. The paper argues further that the whole network of operation in Nigeria has been affected as a result of this ugly phenomenon and it proposes that Ibuanyidanda philosophy which seeks to recognise the potency of the collectively of a social enclave would be a therapeutic healing balm for sound leadership recovery and economic prosperity. The choice of Ibuanyidanda as predicated in this paper is very germane as it does not involve itself in the philosophy of isolation, but believes strongly in the unity of components for progress. It aligns itself with the logic and method of “noetic propaedeutic pedagogy” which simply means the re-examination, re-education of the self for optimal progress and development. Within the ambit of Ibuanyidanda Philosophy, an all- inclusive approach to solving a challenge remains the guiding principle. It evidently abhors the seemingly held view of winner takes all that has characterized and orchestrated the present political system in Nigeria which its negative consequences are economic doom and or slow down. This paper rightly contends that applying Ibuanyidanda Philosophy strict sense will not only navigate the process of economic prosperity but will further ensure all-inclusive environmental atmosphere for leadership participation, gender balance, ethnic/religious tolerance and social cohesion in line with global best practice and 21st century logic of peaceful co-existence. The paper shall adopt critical, analytic, expository and rational methods.